The diffusion coefficient and calibration factors for indoor radon measurement in bare and twin cup modes - Nadir, Ali F.; Juber, Jabbar H.; Subber, Abdul Ridha H.; Al-Hashimi, Noori H.N. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The calibration factor and diffusion are essential parameters in the solid state nuclear track detectors dosimeters. In the present work, experiments were carried out to measure the calibration factors for different modes of measurement in indoor radon dosimetry and diffusion coefficient of gas filter used in the experiments. The calibration chamber provides with standard radium source and radon vision instrument, was used as hybrid combination between active and passive methods. The calibration factor was determined through the relation between standard radon concentration, track density and exposure time. The values of calibration factors was 0.020±0.005 Tr.cm -2 /Bq.m -3 .d for sponge cup mode, 0.021±0.006 Tr.cm -2 / Bq.m -3 .d for filter cup mode and 0.029±0.008 Tr.cm -2 / Bq.m - 3 .d for bare mode respectively. The calibration factor for bare CR-39 was found to be 0.384±0.102 Tr.cm -2 / Bq.m -3 .d. The diffusion coefficients are 7.1x10 -13 m 2 /sec for filter paper and 4.6x10 -9 m 2 /sec for sponge. The calibration of SSNTDs using hybrid method between active and passive can be used to minimize the uncertainty in the calibration factors.
Keywords: Radon; Calibration factor; Diffusion factor; Transmission factor twin cup